Public expenditures on education and health in Belarus before and during the global crisis - Gleb Shymanovich; Dmitrij Kruk (Center for Social and Economic Research (CASE), 2011)
The paper deals with the impact of the global financial crisis on public service delivery - mainly education and healthcare - in Belarus. The pre-crisis period of 2003-2008 was the most prosperous in recent history. These trends resulted in a pretty good fiscal performance. Nevertheless, the share of expenditures on education and healthcare in GDP was decreasing during the 2000s, which was a consequence of demographic trends and a number of reforms in these sectors. The global crisis hurt the Belarusian economy considerably. However, macro-indicators of the Belarusian economy looked pretty good in comparison to other countries, and the deterioration of public finance was limited. Thus, expenditures on both education and healthcare were mainly part of long-term trends and were able to avoid shock adjustments during the crisis. However, there are a number of medium and long-term threats to these public service sectors associated with the crisis agenda. This paper provides a number of policy recommendations to stave off these threats.
Keywords: E62; H50; H51; H52; I18; I22; 330; Fiscal policy; Belarus; Education financing; Health financing; Global economic crisis; Öffentliche Finanzen; Öffentliche Ausgaben; Finanzpolitik; Öffentliche Dienstleistung; Bildungswesen; Bildungsfinanzierung; Gesundheitswesen; Gesundheitskosten; Finanzkrise; Weißrussland